Approaches for the measurement of lateral dimensions of graphene oxide flakes using scanning electron microscopy - Giovanni Chemello; Konstantinos Despotelis; Keith R Paton; Charles A Clifford; Andrew J Pollard; Jörg Radnik; Vasile-Dan Hodoroaba (Nano Express)
There is a practical need, especially from the industrial community, to accurately measure the size and shape of graphene oxide (GO) flakes of commercial origin, in a reliable, simple, and unambiguous way. The sample preparation is a decisive step to obtain a homogeneous distribution of flakes on a substrate, which is suitable for image analysis. A certain level of inhomogeneity was still found but could be accepted for the purpose of this lateral size measurement study. A measurement procedure for Scanning Electron Microscopy (SEM) including sample preparation, measurement, image analysis and reporting was developed and validated to be applied for the lateral size analysis of ‘real-world’ 2D flakes. Samples were produced for analysis by drop casting GO dispersions onto Si/SiO _2 substrates. After SEM imaging, the images were analysed using two approaches to derive size and shape parameters. The influence of different operators has been evaluated. A maximum difference of 10% for the size descriptor and 2% for shape descriptor was found for both image analysis approaches when different samples of the same source material are measured and analysed by the same operator, hence indicating variability caused by sample preparation and analysing different sample areas. When different laboratories/operators perform the image analysis on exactly the same images and same flakes, the deviation found for the size descriptor is 2% and 4.6% corresponding to the two approaches applied, while no difference in the shape descriptor is observed.